Effect of Bias Voltage on the Microstructure and Photoelectric Properties of W-Doped ZnO Films - Haijuan Mei; Wanli Wang; Junfeng Zhao; Weilong Zhong; Muyi Qiu; Jiayang Xu; Kailin Gao; Ge Liu; Jianchu Liang; Weiping Gong (Nanomaterials)
W-doped ZnO (WZO) films were deposited on glass substrates by using RF magnetron sputtering at different substrate bias voltages, and the relationships between microstructure and optical and electrical properties were investigated. The results revealed that the deposition rate of WZO films first decreased from 8.8 to 7.1 nm/min, and then increased to 11.5 nm/min with the increase in bias voltage. After applying a bias voltage to the substrate, the bombardment effect of sputtered ions was enhanced, and the films transformed from a smooth surface into a compact and rough surface. All the films exhibited a hexagonal wurtzite structure with a strong (002) preferred orientation and grew along the c-axis direction. When the bias voltage increased, both the residual stress and lattice parameter of the films gradually increased, and the maximum grain size of 43.4 nm was achieved at −100 V. When the bias voltage was below −300 V, all the films exhibited a high average transmittance of ~90% in the visible light region. As the bias voltage increased, the sheet resistance and resistivity of the films initially decreased and then gradually increased. The highest FOM of 5.8 × 10−4 Ω−1 was achieved at −100 V, possessing the best comprehensive photoelectric properties.